2023
DOI: 10.1177/13621688231152194
|View full text |Cite
|
Sign up to set email alerts
|

Whose English should be talked and taught? Views from international English teachers in Thai higher education

Abstract: This qualitative study aimed to explore the perceptions of 12 international English teachers (from the UK, the USA, Australia, Indonesia, and the Philippines at four universities in Thailand) towards World Englishes (WE), Thai English (TE), and the feasibility of incorporating WE into English language teaching (ELT) classrooms. Based on semi-structured interviews and qualitative content analysis, findings revealed that the participants demonstrated positive views and did not deny the existence of WE and TE, al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 55 publications
0
1
0
Order By: Relevance
“…A significant gap in the current Thai marketing education system lies in its predominant focus on micro-level perspectives (Crocco, 2018), which center on individual transactions, product promotion, and short-term profitability (Boonsuk, Wasoh & Waelateh, 2023). This narrow focus often disregards the broader societal and environmental consequences of marketing decisions (Hunt, 1976).…”
Section: Emphasis On Micro-level Perspectivesmentioning
confidence: 99%
See 3 more Smart Citations
“…A significant gap in the current Thai marketing education system lies in its predominant focus on micro-level perspectives (Crocco, 2018), which center on individual transactions, product promotion, and short-term profitability (Boonsuk, Wasoh & Waelateh, 2023). This narrow focus often disregards the broader societal and environmental consequences of marketing decisions (Hunt, 1976).…”
Section: Emphasis On Micro-level Perspectivesmentioning
confidence: 99%
“…Ethical considerations and social responsibilities are integral components of modern marketing practices. However, the current Thai marketing education system tends to overlook these dimensions, placing more emphasis on technical skills and tactical approaches (Boonsuk, Wasoh & Waelateh, 2023). This gap leaves students ill-prepared to address ethical challenges and societal implications associated with marketing decisions (Drumwright, 1994).…”
Section: Lack Of Ethical and Social Contextmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of icebreakers may align well with this shift in teaching strategies, as they encourage student interaction and collaboration. However, there is a lack of research on the effectiveness of icebreakers in promoting student participation and engagement in the Philippine context A study conducted by Boonsuk, et al (2023) explored the perceptions of Filipino students towards icebreakers. The study found that students perceived icebreakers to be effective in promoting social connections and enhancing their learning experience.…”
Section: Effectiveness Of Icebreakers In the Philippine Contextmentioning
confidence: 99%